The effect of support type on water-gas shift kinetics over Pt based trimetallic systems - İbrahimov, Nijat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
The aim of the current study is to determine the power law type rate expressions of water-gas shift (WGS) reaction over 1Pt-1Re-1Na/CeO2 and 1Pt-1Re-1Na/TiO2 catalysts under realistic feed conditions. In this context, the 1Pt-1Re-1Na/CeO2 and 1Pt-1Re-1Na/TiO2 samples were prepared by using sequential incipient-to-wetness impregnation (IWI) method. The preliminary kinetic tests were conducted to determine the experimental conditions guaranteeing kinetically controlled and mass transfer limitation free zone. The kinetic experiments were performed at 350 °C and an atmospheric pressure, with H2O/CO feed ratio ranging between 15 and 45. For each sample, 15 pairs of kinetic experiments, for which partial pressures of CO, H2O, H2, CO2 and CH4, and residence time (Wcat/FCO) were changed according to an experimental design. The values for the experimental initial rates were used to evaluate kinetic parameters of the power law type rate expressions. The reaction orders for CO, H2O, H2 and CO2 were calculated as 0.79, 0.24, -0.30 and -0.31, respectively, within ±7% error over the CeO2 supported catalyst through non-linear regression analysis in MATLABTM, while the orders were estimated as 0.57, 0.45, -0.30 and -0.32 for the same sequence over the TiO2 supported sample within ±9% error. This study also revealed that changes in CH4 partial pressure have negligible effect on the reaction rates obtained for both samples. Based on the reaction orders estimated for both catalysts, it can be concluded that CeO2 supported sample is more sensitive to CO, which is more likely due to high oxygen storage capacity of ceria, while the opposite is true for TiO2. The apparent activation energies and the frequency factors were calculated as 51.07 kJ mol-1 and 947.90 μmol mgcat-1 s-1 kPa-0.42, respectively for 1Pt-1Re-1Na/CeO2, while those were found to be 69.53 kJ mol-1 and 446.01 μmol mgcat-1 s-1 kPa-0.40 for 1Pt-1Re-1Na/TiO2, in the temperature range of 300-350 ºC.
Keywords: Water-gas.